Child Sexual Abuse: How Is the Victim Represented in Portuguese Sentences - Pereira, Bárbara (Victims & offenders, 2024)
Child sexual abuse (CSA) is a global problem with severe consequences for victims and their development, with various resulting consequences. Sentences regarding CSA crimes can be unconsciously influenced by extralegal factors. This study aimed to understand how Portuguese CSA victims are represented in judges’ sentencing of offenders. Twenty-seven sentences of CSA, from a Portuguese database, were thoroughly analyzed through thematic analysis. Six main themes pertaining to the victim, emerged from the sentences’ analysis: (i) emotional response during statements; (ii) reported details and reactions; (iii) credibility and reliability of statements; (iv) revelation and secret-keeping; (v) victim’s trajectory; and (vi) impact on the victim. The assessment of the credibility of the victim’s statements proved to be central across all sentences. Data related to external sources, namely judges’ personal beliefs, physical evidence, and witnesses, emerged. Legal and psychosocial factors were identified, with the latter consisting of victim-blaming and legitimization of sexual violence. As for the practical implications of these findings, we argue that a fair exercise of justice, and improvement of the efficacy of prosecution of CSA is only possible through identification of these sensitive issues and adequate addressal of them during magistrates’ training.